SISTEM PEREKONOMIAN NEGARA-NEGARA DI DUNIA - Dicky Sumarsono (Jurnal Akuntansi dan Pajak, 2016)
This study aims to look at the existing economic system in this world, both socialist economic system, capitalist economic system, and Islamic economic system. The research method used is literature study method. The results of the study indicate that the socialist economic system, the economic system in which the government has a very big role in managing the wheels of the economy from upstream to downstream in the economic chain in society, and this economic system has not existed or not developed since the collapse of the soviet union. While the capitalist economic system, the economic system gives people the freedom to own wealth, and this system also dominates the economic systems used by countries in this world. Then the Islamic economic system until recently is a concept that will be an alternative to the economic system that prosper with a lot of learning also from the two existing economic system, namely the capitalist economic system and socialist economic system, of course take things positive of both as long as it is not against the Islamic Shari'ah that comes from the sources of Islamic law especially the Qur'an and al-Hadis.